Pollen percentages, tree abundances and the Fagerlind effect - Prentice,IC; Webb,T (Journal of Quaternary Science, 1986)
Pollen diagrams traditionally are read as if pollen percentages were linearly related to relative tree abundances, although the slopes and intercepts of these relationships are accepted to differ among taxa. Corresponding map patterns of modern pollen and tree percentages support this assumption of linearity, which also underlies the use of linear regression on percentage data for pollentree calibration. Fagerlind, however, showed that the theoretical relationship need not be linear and may be confounded by interdependencies among taxa. Regressions and scatter plots of modern pollen and tree percentages are here compared with results of extended Rvalue (ERV) models, which correct for the ‘Fagerlind effect’. Three data sets from Wisconsin and Michigan, USA illustrate that regression coefficients provide a first approximation to their ERV equivalents, but scatter plots derived from the ERV analyses show reduced scatter about linearised relationships. Copyright © 1986 John Wiley & Sons, Ltd